Flexible cellulose nanocrystalline composite film as well as preparation method and application thereof

By introducing cross -linked agents, surfactants and fragrance -type compounds in the cellulose nanocrystalline composite film, combined with PH adjustment, it solves the problem of rapid response, repeated rubbing, and time dependencies in existing technologies. The time dependence and repeated rubbing capacity of flexible cellulose nano crystal composite membrane are implemented, which is suitable for information storage and encryption anti -counterfeiting.

CN119371706AActive Publication Date: 2025-01-28SHANGHAI JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411958088.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The prior art is difficult to develop a fast-responsive, simple preparation, mild conditions, repeatable erase storage material, especially in the time dimension to regulate fluorescence characteristics and realize repeatable writing/erase of information.

Method used

By introducing cross -linked agents and surfactants in cellulose nanocrystal, prepare a cellulose nanocrystalline composite film with good flexibility and structural color, and to introduce the incense beanin -type compounds and adjust the pH value to achieve its fluorescent characteristics Enhance or disappear, thereby realizing the function of repeated writing or erasing.

Benefits of technology

The time dependence and repeated rubbing capacity of flexible cellulose nano crystal composite membrane can be achieved. It can display obvious time in ultraviolet light to rely on blue fluorescence, and achieve rapid repeated rubbing writing through the acid -base solution. It is suitable for information storage And encrypted anti -counterfeiting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371706A_ABST
    Figure CN119371706A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional polymer composite films, and provides a preparation method of a time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film, which comprises the following steps: S1, preparing a cellulose nanocrystal film with a structural color; s2, preparing a flexible cellulose nanocrystalline composite film which is dependent on time and can be repeatedly erased and written; and an optional step S3: preparing the time-dependent and repeatedly erasable flexible cellulose nanocrystalline composite film treated by quaternary ammonium salt. The invention further relates to a time-dependent and rewritable flexible cellulose nanocrystalline composite film, an information storage material, an anti-counterfeiting encryption material and an anti-counterfeiting encryption method. The flexible cellulose nanocrystal composite film has good flexibility and mechanical properties and bright and uniform structural color, fluorescence of the flexible cellulose nanocrystal composite film can be enhanced or disappeared by adjusting the pH value, and the function of repeated writing or erasing is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional polymer composite membranes, and in particular to a flexible cellulose nanocrystal composite membrane with time dependence and repeatable erasability that can be used for information storage and encryption anti-counterfeiting, as well as a preparation method and application thereof. Background Art

[0002] Today, the rapid increase in information content has brought about urgent information security issues. In daily life, how to effectively protect information from being stolen, tampered with or forged during various transmission processes is an issue that is receiving increasing attention. This situation not only strengthens the demand for new materials and technologies for information anti-counterfeiting encryption and secure storage in modern society, but also requires increasingly diversified new anti-counterfeiting materials and technologies.

[0003] In recent years, researchers have been committed to preparing new optical anti-counterfeiting encryption and secure storage materials with different functions through different construction strategies to ensure information security. Among them, information functional materials with both structural color and fluorescence have become a research hotspot due to their unique performance advantages, and have great potential for wide application in information anti-counterfeiting and storage technologies. Cellulose nanocrystals (CNC), as a green and environmentally friendly natural polymer, have the advantages of abundant reserves, degradability and renewability, and are an ideal photonic crystal for constructing structural color materials. Water-dispersed CNC suspensions can spontaneously assemble into chiral cholesteric phase structures at appropriate concentrations, and retain this structure in dry solid films. As a result, CNC-based films can not only reflect visible light of specific wavelengths, but also serve as a chiral environment for luminophores to generate circularly polarized light. Furthermore, the chiral cholesteric phase structure of CNC-based films has excellent stimulus response characteristics. For example, under the stimulation of stress, solvent, moisture, pH, light, electricity, magnetism, heat, etc., its helical pitch P can change, resulting in corresponding changes in its structural color and circularly polarized luminescence. This provides favorable conditions for the development of adjustable CNC-based information security materials. However, due to its crystalline six-membered cyclic polysaccharide molecular chain structure and abundant hydrogen bonding, CNC solid films usually have the defects of being hard and brittle, which makes it difficult to meet objective use requirements.

[0004] Combining fluorescence with structural color is the main method to break the single optical mode of CNC-based films, which can increase the difficulty of information decoding and improve the level of information security. To date, various typical stimulus-responsive fluorescent materials that achieve fluorescence or color changes through stimuli such as light, heat, stress, pH, and ions have been developed and used for information encryption and anti-counterfeiting. Although these materials show great application potential in anti-counterfeiting and information encryption, most of them can only achieve constant fluorescence characteristics and are difficult to regulate in the time dimension. On the other hand, under the conditions of the presence or removal of specific external stimuli, the writing and erasing of information stored in information security functional materials is also an important issue. However, most of the reported erasable materials rely on chemical reaction activity or are based on gel material systems, and their rewritability and sensitivity are limited.

[0005] Therefore, it is necessary to develop a fast-response, simple-to-prepare, mild-condition, and rewritable information security storage material. In summary, based on CNC, it is of great practical significance to develop a rewritable, time-dependent structural color-fluorescence flexible functional material that can be used for information recording storage and encryption anti-counterfeiting. Summary of the invention

[0006] The purpose of the present application is to provide a time-dependent and rewritable flexible cellulose nanocrystal composite film and its preparation method and application. Specifically, by introducing a crosslinking agent and a surfactant into the cellulose nanocrystal, the cellulose nanocrystal composite film has good flexibility and a bright and uniform structural color, and by introducing a coumarin compound, the flexible cellulose nanocrystal composite film has a fluorescent property. The fluorescence can be enhanced or eliminated by adjusting the pH value, thereby achieving the function of rewritable or erasable.

[0007] In order to solve the above technical problems, this application provides the following technical solutions.

[0008] In a first aspect, the present application provides a method for preparing a time-dependent and rewritable flexible cellulose nanocrystal composite film, the preparation method comprising the following steps: Step S1: Preparation of cellulose nanocrystal film with structural color Mixing a required weight of a water-dispersible cellulose nanocrystal suspension, a first crosslinking agent, a first surfactant, a coumarin compound, and a first photoinitiator to form a uniform mixed suspension, and drying to obtain a cellulose nanocrystal film with structural color; Step S2: Preparation of time-dependent and rewritable flexible cellulose nanocrystal composite films The cellulose nanocrystal film with structural color obtained in step S1 is placed under ultraviolet light for a first cross-linking reaction to obtain the time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film.

[0009] In one embodiment of the first aspect, the preparation method further comprises the following steps: Step S3: Preparation of time-dependent and rewritable flexible cellulose nanocrystal composite films treated with quaternary ammonium salts Soaking the time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film obtained in step S2 with a soaking liquid, and then placing it under ultraviolet light for a second cross-linking reaction to obtain a quaternary ammonium salt-treated time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film; Wherein, the soaking liquid is made of a second cross-linking agent, a quaternary ammonium salt ionic liquid, a second photoinitiator and an aqueous mixed solvent.

[0010] In one embodiment of the first aspect, in step S1, the water-dispersible cellulose nanocrystal suspension is prepared from cellulose by a mature sulfuric acid hydrolysis method, and its mass fraction of the total mass of the raw materials added in this step is 50-90%. Preferably, the mass fraction of the water-dispersible cellulose nanocrystal suspension in the total mass of the raw materials added in this step is 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or a range or sub-range between any two of them.

[0011] Preferably, in step S1, the first cross-linking agent is one or both of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate, the average relative molecular mass of the first cross-linking agent is 200g / mol-4000g / mol, and its mass fraction of the total mass of the raw materials added in this step is 5% to 30%. Preferably, the average relative molecular mass of the first cross-linking agent is 200g / mol, 500g / mol, 1000g / mol, 1500g / mol, 2000g / mol, 2500g / mol, 3000g / mol, 3500g / mol, 4000g / mol or a range or sub-range between any two of them. Preferably, the mass fraction of the first cross-linking agent in the total mass of the raw materials added in this step is 5%, 10%, 15%, 20%, 25%, 30% or a range or sub-range between any two of them.

[0012] Preferably, in step S1, the first surfactant is at least one of alkyl sulfate with 8-18 carbon atoms, alkyl sulfonate with 8-18 carbon atoms, and alkylbenzene sulfonate with 8-18 carbon atoms, and its mass fraction of the total mass of the raw materials added in this step is 0% to 8%. The number of carbon atoms of the alkyl group in the first surfactant is 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18. Preferably, the mass fraction of the first surfactant in the total mass of the raw materials added in this step is 0%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8% or the range or sub-range between any two of them.

[0013] Preferably, in step S1, the first photoinitiator is any commercially available universal ultraviolet photoinitiator, and the mass fraction of the total mass of the raw materials added in this step is 0.5% to 4.5%. The mass fraction of the first photoinitiator in the total mass of the raw materials added in this step is 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, or a range or sub-range between any two of these values.

[0014] In one embodiment of the first aspect, in step S1, the coumarin compound is one or more of the compounds described in the following structural formulas (I) to (IV), and the mass fraction of the total mass of the raw materials added in this step is 0.5% to 7.5%: .

[0015] Preferably, the mass fraction of the coumarin compound in the total mass of the raw materials added in this step is 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5% or a range or sub-range between any two of them.

[0016] In one embodiment of the first aspect, in step S3, the second cross-linking agent is one or both of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate, the average relative molecular mass of the second cross-linking agent is 200g / mol-4000g / mol, and the mass fraction thereof in the total mass of the raw materials added in this step is 0.5%-5%. Preferably, the mass fraction of the second cross-linking agent in the total mass of the raw materials added in this step is 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, or a range or sub-range between any two of these values.

[0017] Preferably, in step S3, the second photoinitiator is any commercially available universal ultraviolet photoinitiator, and its mass fraction of the total mass of the raw materials added in this step is 0.1% to 1%. Preferably, the mass fraction of the second photoinitiator of the total mass of the raw materials added in this step is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or the range or sub-range between any two of them.

[0018] Preferably, in step S3, the aqueous mixed solvent is a mixture of water and dimethyl sulfoxide.

[0019] In one embodiment of the first aspect, in step S3, the quaternary ammonium salt ionic liquid is one or both of quaternary ammonium acrylate and quaternary ammonium methacrylate, and the mass fraction of the total mass of the raw materials added in this step is 10% to 60%, and the structure of the quaternary ammonium salt ionic liquid is shown as follows: ; Wherein, m is an integer of 1 to 4, R1 is H or methyl, R2, R3 and R4 are methyl, ethyl, propyl, butyl or benzyl, and R2, R3 and R4 may be the same or different, and X is chlorine or bromine.

[0020] In one implementation of the first aspect, in step S3, the soaking time is 6 to 72 hours, preferably by reduced pressure or vacuum soaking.

[0021] Preferably, when performing the second cross-linking reaction, the ultraviolet light irradiation time does not exceed 0.5 hours.

[0022] In a second aspect, the present application provides a time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film, which is prepared by the preparation method as described in the first aspect.

[0023] In a third aspect, the present application provides an information storage material comprising the time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film as described in the second aspect.

[0024] In a fourth aspect, the present application provides an anti-counterfeiting encryption material, which comprises the time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film as described in the second aspect.

[0025] In the fifth aspect, the present application provides an anti-counterfeiting encryption method, which includes the following steps: storing the information to be hidden on the anti-counterfeiting material as described in the fourth aspect, then infiltrating the anti-counterfeiting encryption material with an alkaline solution, and displaying the information to be hidden under ultraviolet light.

[0026] Compared with the prior art, the positive effect of the present invention is that the flexible cellulose nanocrystal composite film (also referred to as a flexible structural color-fluorescent composite film) of the present invention has good flexibility and mechanical properties, and the structural color is bright and uniform. On the one hand, when infiltrated with a dilute alkaline solution, it can show obvious time-dependent blue fluorescence under ultraviolet light. When further infiltrated again with a dilute acid solution, the fluorescence disappears immediately, showing the characteristics of repeatable writing / erasing. On the other hand, when the flexible structural color-fluorescent composite film is irradiated with ultraviolet light using a mask method, the template pattern can be transferred to the film to achieve a photoinduced pattern. Therefore, the flexible structural color-fluorescent composite film of the present invention as described above can be used as a new type of cellulose nanocrystal-based information storage and encryption anti-counterfeiting functional material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The following figures describe in detail the exemplary embodiments disclosed in this application. The same reference numerals represent similar structures in several views of the drawings. Those skilled in the art will understand that these embodiments are non-limiting, exemplary embodiments, and the drawings are only for the purpose of illustration and description, and are not intended to limit the scope of this application. Other embodiments may also accomplish the inventive intent in this application. It should be understood that the drawings are not drawn to scale.

[0028] Figure 1 This is a photo of the flexible structural color-fluorescence composite film prepared in Example 1 and Example 2 of the present invention; Figure 2 This is a photo of the flexible structural color-fluorescence composite film prepared in Example 3-5 of the present invention; Figure 3 (a) reflection spectrum and (b) stress-strain curve of the flexible structural color-fluorescence composite film prepared in Example 1 and Example 2 of the present invention; Figure 4 The photograph and fluorescence spectrum of the flexible structural color-fluorescent composite film prepared in Example 2 of the present invention after repeated writing / erasing under ultraviolet light; Figure 5 The alkali direct writing pattern of the flexible structural color-fluorescent composite film prepared in Example 1 and Example 2 of the present invention under ultraviolet light; Figure 6 The light-induced two-dimensional code information storage of the flexible structural color-fluorescence composite film prepared in Example 1 of the present invention; Figure 7 Schematic diagram of information storage and encryption anti-counterfeiting of the flexible structural color-fluorescent composite film prepared in Example 2 of the present invention under ultraviolet light. DETAILED DESCRIPTION

[0029] Unless otherwise indicated, implied from the context, or customary in the prior art, all parts and percentages in this application are based on weight, and the test and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application or publication referred to in this application are fully incorporated herein by reference, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, product and processing designs, polymers, comonomers, initiators or catalysts disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.

[0030] The numerical ranges in this application are approximate values, so unless otherwise specified, they may include values ​​outside the range. Numerical ranges include all values ​​from the lower limit to the upper limit increased by 1 unit, provided that there is an interval of at least 2 units between any lower value and any higher value. For example, if the recorded component, physical or other properties (such as molecular weight, melt index, etc.) are 100 to 1000, it means that all single values ​​are clearly listed, such as 100, 101, 102, etc., and all sub-ranges, such as 100 to 166, 155 to 170, 198 to 200, etc. For a range containing a value less than 1 or containing a fraction greater than 1 (such as 1.1, 1.5, etc.), 1 unit is appropriately regarded as 0.0001, 0.001, 0.01 or 0.1. For a range containing a single digit less than 10 (such as 1 to 5), 1 unit is usually regarded as 0.1. These are only specific examples of what is intended to be expressed, and all possible combinations of values ​​between the lowest and highest values ​​listed are considered to be clearly recorded in this application. It should also be noted that the terms "first", "second", etc. in this article do not limit the order of precedence, but are only used to distinguish substances with different structures.

[0031] When used with respect to chemical compounds, unless expressly specified otherwise, the singular includes all isomeric forms and vice versa (e.g., "hexane" includes all isomers of hexane, individually or collectively). In addition, nouns using "a," "an," or "the" also include their plural forms unless expressly specified otherwise.

[0032] The terms "comprising", "including", "having" and their derivatives do not exclude the presence of any other components, steps or processes, and are irrelevant to whether these other components, steps or processes are disclosed in this application. To eliminate any doubt, unless explicitly stated, all compositions using the terms "comprising", "including", or "having" in this application may include any additional additives, adjuvants or compounds. On the contrary, except for those necessary for operating performance, the term "essentially consisting of..." excludes any other components, steps or processes from the scope of any description of the term below. The term "consisting of..." does not include any components, steps or processes that are not specifically described or listed. Unless explicitly stated, the term "or" refers to the listed individual members or any combination thereof.

[0033] The demand for diversity and security of information transmission in modern society is increasing, which has led to the rapid development of new materials and technologies for information storage, encryption and anti-counterfeiting. Seeking more diverse information storage and encryption anti-counterfeiting functional materials is a fundamental solution to information security issues. Based on this, the present invention provides a flexible cellulose nanocrystal composite film (hereinafter referred to as a flexible structural color-fluorescent composite film) with time dependence and repeatable writing / erasing ability, wherein the flexible structural color-fluorescent composite film is made of CNC, polyethylene glycol diacrylate PEGDA (polyethylene glycol dimethacrylate PEGDMA), surfactants, coumarin compounds, photoinitiators, (and / or) quaternary ammonium salts of acrylates (quaternary ammonium salts of methacrylates). PEGDA or PEGDMA mainly plays a cross-linking role and gives the structural color-fluorescent composite film excellent flexibility. The surfactant can adjust the dispersibility and compatibility of the system, so that the film has a uniform iridescent structural color. Due to the inherent sensitivity of the fluorescence of the coumarin compounds to pH, the flexible structural color-fluorescent composite film has excellent direct writing and erasing capabilities. In addition, quaternary ammonium acrylate (quaternary ammonium methacrylate) is an ionic liquid. After being compounded into the film, the obtained film has better hydrophilicity. When writing, the aqueous solution can quickly and evenly penetrate into the film, thereby inhibiting the internal stress deformation caused by uneven diffusion of water in the film.

[0034] In the composition of the flexible structural color-fluorescent composite film, the CNC is prepared from cellulose by a mature sulfuric acid hydrolysis method, and its mass fraction is not less than 50% (excluding the mass of quaternary ammonium acrylate or quaternary ammonium methacrylate).

[0035] In the composition of the flexible structural color-fluorescent composite film, the PEGDA and PEGDMA have an average relative molecular mass of 200 g / mol to 4000 g / mol, a mass fraction of 5% to 30% (excluding the mass of quaternary ammonium acrylate or quaternary ammonium methacrylate), and the structural formulas are as follows: .

[0036] In the composition of the flexible structural color-fluorescent composite film, the surfactant is an alkyl sulfate, an alkyl sulfonate, or an alkylbenzene sulfonate, and its mass fraction is 0% to 8% (excluding the mass of quaternary ammonium acrylate or quaternary ammonium methacrylate), and the alkyl group is an alkane group with 8 to 18 carbon atoms.

[0037] In the composition of the flexible structural color-fluorescent composite film, the coumarin compound is any one of the following structural formulas (I) to (IV), and its mass fraction is 0.5% to 7.5% (excluding the mass of quaternary ammonium acrylate or quaternary ammonium methacrylate): .

[0038] In the composition of the flexible structural color-fluorescent composite film, the photoinitiator is any commercially available universal ultraviolet photoinitiator, and its mass fraction is 0.5% to 4.5% (excluding the mass of quaternary ammonium acrylate or quaternary ammonium methacrylate).

[0039] In the composition of the flexible structural color-fluorescent composite film, the quaternary ammonium acrylate salt and the quaternary ammonium methacrylate salt have structures shown as follows: ; Wherein, m is an integer of 1 to 4, R1 is H or methyl, R2, R3 and R4 are methyl, ethyl, propyl, butyl or benzyl, and R2, R3 and R4 may be the same or different, and X is chlorine or bromine.

[0040] In addition, the present invention also provides a method for preparing the flexible structural color-fluorescent composite film having time dependence and repeatable writing / erasing capability as described above, the method comprising the following steps: (1) adding a water-dispersible CNC suspension, polyethylene glycol diacrylate PEGDA (polyethylene glycol dimethacrylate PEGDMA), a surfactant, a coumarin compound and a photoinitiator into a sealable container according to the required mass, and then magnetically stirring at room temperature until the coumarin compound is completely dissolved (or fully dispersed) to form a uniform mixed suspension; (2) Pour the mixed suspension into a petri dish and place the petri dish naturally at room temperature until the mixed suspension is completely dried to form a film with structural color; (3) placing the obtained film with structural color under ultraviolet light for cross-linking reaction to form a cross-linked flexible structural color-fluorescent composite film I; (4) taking the required mass of polyethylene glycol diacrylate PEGDA (polyethylene glycol dimethacrylate PEGDMA), quaternary ammonium acrylate (quaternary ammonium methacrylate), photoinitiator, dimethyl sulfoxide DMSO and water to prepare an immersion solution of a certain concentration; (5) immersing the cross-linked flexible structural color-fluorescent composite film I obtained in step (3) in an immersion liquid; (6) After the immersion is completed, the film is taken out, the surface is rinsed with ethanol, and then placed under ultraviolet light for a secondary cross-linking reaction to obtain a quaternary ammonium salt-treated cross-linked flexible structural color-fluorescent composite film II.

[0041] As the preparation method of the flexible structural color-fluorescent composite film of the present invention, in the step (1), the water-dispersible CNC suspension is prepared from cellulose by a mature sulfuric acid hydrolysis method, and its mass fraction is not less than 50% (excluding the mass of quaternary ammonium acrylate or quaternary ammonium methacrylate); As the preparation method of the flexible structural color-fluorescent composite film of the present invention, in the step (1), the average relative molecular mass of PEGDA and PEGDMA is 200g / mol~4000g / mol, the mass fraction is 5%~30% (excluding the mass of quaternary ammonium salt of acrylate or quaternary ammonium salt of methacrylate), and the structural formulas are as follows: .

[0042] As the preparation method of the flexible structural color-fluorescent composite film of the present invention, in the step (1), the surfactant is an alkyl sulfate, an alkyl sulfonate, or an alkylbenzene sulfonate, and its mass fraction is 0% to 8% (excluding the mass of the quaternary ammonium salt of acrylate or the quaternary ammonium salt of methacrylate), and the alkyl group is an alkane group with 8 to 18 carbon atoms.

[0043] As the preparation method of the flexible structural color-fluorescent composite film of the present invention, in the step (1), the coumarin compound is any one of the following structural formulas (I) to (IV), and its mass fraction is 0.5% to 7.5% (excluding the mass of quaternary ammonium salt of acrylate or quaternary ammonium salt of methacrylate): .

[0044] As the preparation method of the flexible structural color-fluorescent composite film of the present invention, in the step (1), the photoinitiator is any commercially available universal ultraviolet photoinitiator, and its mass fraction is 0.5% to 4.5% (excluding the mass of quaternary ammonium acrylate or quaternary ammonium methacrylate).

[0045] As the method for preparing the flexible structural color-fluorescent composite film of the present invention, in the step (3), the ultraviolet light irradiation time is related to the light intensity and is not specifically limited, as long as the film can be cross-linked and has good flexibility.

[0046] As the preparation method of the flexible structural color-fluorescent composite film of the present invention, in the step (4), the average relative molecular mass of PEGDA and PEGDMA is 200 g / mol~4000 g / mol, the mass fraction is 0.5%~5%, and the structural formulas are as follows: .

[0047] As the preparation method of the flexible structural color-fluorescent composite film of the present invention, in the step (4), the mass fraction of the quaternary ammonium salt of acrylate and the quaternary ammonium salt of methacrylate is 10% to 60%, and the structure is shown as follows: ; Wherein, m is an integer of 1 to 4, R1 is H or methyl, R2, R3 and R4 are methyl, ethyl, propyl, butyl or benzyl, and R2, R3 and R4 may be the same or different, and X is chlorine or bromine.

[0048] As the method for preparing the flexible structural color-fluorescent composite film of the present invention, in the step (4), the photoinitiator is any commercially available universal ultraviolet photoinitiator, and its mass fraction is 0.1% to 1%.

[0049] As the preparation method of the flexible structural color-fluorescent composite film of the present invention, in the step (4), except for PEGDA and PEGDMA, quaternary ammonium acrylate and quaternary ammonium methacrylate, and photoinitiator, the remaining components are DMSO and / or water, and the ratio between the two is not limited.

[0050] As the method for preparing the flexible structural color-fluorescent composite film of the present invention, in the step (5), the immersion time is 6 to 72 hours, and reduced pressure (or even vacuum) immersion can be used as needed.

[0051] In the method for preparing the flexible structural color-fluorescent composite film of the present invention, in the step (6), the ultraviolet light irradiation time does not exceed 0.5 hours.

[0052] As the method for preparing the flexible structural color-fluorescent composite film of the present invention, steps (4) to (6) can be discarded according to actual needs, and the film I obtained in step (3) and / or the film II obtained in step (6) are both the flexible structural color-fluorescent composite film of the present invention.

[0053] The flexible structural color-fluorescent composite film of the present invention has good flexibility and mechanical properties, and the structural color is bright and uniform. On the one hand, when soaked in a dilute alkaline solution, it can show obvious time-dependent blue fluorescence under ultraviolet light. When further soaked in a dilute acid solution again, the fluorescence disappears immediately, showing the characteristics of repeatable writing / erasing. On the other hand, when the flexible structural color-fluorescent composite film is irradiated with ultraviolet light using a mask method, the template pattern can be transferred to the film to achieve photopatterning. Therefore, the flexible structural color-fluorescent composite film of the present invention as described above can be used as a new type of CNC-based information storage and encryption anti-counterfeiting functional material.

[0054] Example The following will be combined with the embodiments of the present application to clearly and completely describe the technical solution of the present application. Unless otherwise specified, the reagents and raw materials used can be purchased through commercial channels. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications.

[0055] Example 1 Take 50g of CNC suspension with a mass concentration of about 2.1% in a glass bottle with a lid, add 1g of PEGDA with a mass concentration of 25% (average relative molecular mass of 1000g / mol), 1g of sodium dodecyl sulfate with a mass concentration of 5%, 0.05g of coumarin compound (structural formula IV as described above) and 0.025g of photoinitiator I2959, then cover the bottle cap and magnetize at room temperature until the coumarin compound is completely dissolved. Thereafter, pour the mixed suspension into a plastic culture dish with a diameter of about 115mm, and evaporate naturally at room temperature until it is completely dried to form a film with structural color. Finally, place the plastic culture dish with the structural color film under 365nm ultraviolet light for a cross-linking reaction for 15min to obtain the flexible structural color-fluorescent composite film I.

[0056] Example 2 Take 50g of CNC suspension with a mass concentration of about 2.1% in a glass bottle with a lid, add 1g of PEGDA with a mass concentration of 25% (average relative molecular mass of 1000g / mol), 1g of sodium dodecyl sulfate with a mass concentration of 5%, 0.05g of coumarin compound (structural formula IV as described above) and 0.025g of photoinitiator I2959, cover the bottle cap, and magnetize at room temperature until the coumarin compound is completely dissolved. Then pour the mixed suspension into a plastic culture dish with a diameter of about 115mm, and evaporate naturally at room temperature until it is completely dried to form a film with structural color. Thereafter, place the plastic culture dish with the structural color film under 365nm ultraviolet light for a cross-linking reaction for 15min to obtain a cross-linked flexible structural color-fluorescent composite film I. In addition, 50g of 80% mass concentration of quaternary ammonium acrylate salt (structural formula as described above, m is 2, R1 is H, R2, R3 and R4 are all methyl, X is chlorine), 6.25g of 25% mass concentration of PEGDA (average relative molecular mass is 1000g / mol), 0.625g of photoinitiator I2959, 37.6g of DMSO, and 12.4g of water are prepared into a uniform soaking solution. Further, the cross-linked flexible structural color-fluorescent composite film I is immersed in the soaking solution for 24h, and the vacuum degree is maintained at no more than -0.095MPa. After soaking, the film surface is rinsed with ethanol, and then irradiated with 365nm ultraviolet light for 5min. Thus, the flexible structural color-fluorescent composite film II is obtained.

[0057] Example 3 Take 50g of CNC suspension with a mass concentration of about 2.1% in a glass bottle with a lid, add 1g of PEGDA with a mass concentration of 25% (average relative molecular mass of 1000 g / mol), 1g of sodium octadecyl sulfate with a mass concentration of 5%, 0.01g of coumarin compound (structural formula III as described above) and 0.025g of photoinitiator I2959, cover the bottle cap, and magnetize at room temperature until the coumarin compound is completely dissolved. Then pour the mixed suspension into a plastic culture dish with a diameter of about 115mm, and evaporate naturally at room temperature until it is completely dried to form a film with structural color. Thereafter, place the plastic culture dish with the structural color film under 365nm ultraviolet light for cross-linking reaction for 15min to obtain a cross-linked flexible structural color-fluorescent composite film I. In addition, 50g of 80% mass concentration of quaternary ammonium acrylate salt (structural formula as described above, m is 2, R1 is H, R2, R3 and R4 are all methyl, X is chlorine), 6.25g of 25% mass concentration of PEGDA (average relative molecular mass is 1000 g / mol), 0.625g of photoinitiator I2959, 37.6g of DMSO, and 12.4g of water are prepared into a uniform soaking solution. Further, the cross-linked flexible structural color-fluorescent composite film I is immersed in the soaking solution for 24h, and the vacuum degree is maintained at no more than -0.095MPa. After soaking, the film surface is rinsed with ethanol, and then irradiated with 365nm ultraviolet light for 5min. Thus, the flexible structural color-fluorescent composite film II is obtained.

[0058] Example 4 Take 50g of CNC suspension with a mass concentration of about 2.1% in a glass bottle with a lid, add 1g of PEGDMA with a mass concentration of 25% (average relative molecular mass of 1000 g / mol), 1g of sodium dodecyl sulfate with a mass concentration of 5%, 0.01g of coumarin compound (structural formula II as described above) and 0.025g of photoinitiator I2959, cover the bottle cap, and magnetize at room temperature until the coumarin compound is completely dissolved. Then pour the mixed suspension into a plastic culture dish with a diameter of about 115mm, and evaporate naturally at room temperature until it is completely dried to form a film with structural color. Thereafter, place the plastic culture dish with the structural color film under 365nm ultraviolet light for cross-linking reaction for 15min to obtain a cross-linked flexible structural color-fluorescent composite film I.

[0059] Example 5 Take 50g of CNC suspension with a mass concentration of about 2.1% in a glass bottle with a lid, add 1g of PEGDMA with a mass concentration of 25% (average relative molecular mass of 1000g / mol), 1g of sodium dodecylbenzene sulfonate with a mass concentration of 5%, 0.01g of coumarin compound (structural formula I as described above) and 0.025g of photoinitiator I2959, cover the bottle cap, and magnetize at room temperature until the coumarin compound is completely dissolved. Then pour the mixed suspension into a plastic culture dish with a diameter of about 115mm, and evaporate naturally at room temperature until it is completely dried to form a film with structural color. Thereafter, place the plastic culture dish with the structural color film under 365nm ultraviolet light for a cross-linking reaction for 15min to obtain a cross-linked flexible structural color-fluorescent composite film I. In addition, 50g of 80% quaternary ammonium methacrylate (as described above, m is 2, R1 is methyl, R2, R3 and R4 are all methyl, X is chlorine), 6.25g of 25% PEGDMA (average relative molecular mass is 1000g / mol), 0.625g of photoinitiator I2959, 37.6g of DMSO, and 12.4g of water are prepared into a uniform soaking solution. Further, the cross-linked flexible structural color-fluorescent composite film I is immersed in the soaking solution for 24h, and the vacuum degree is maintained at no more than -0.095MPa. After soaking, the film surface is rinsed with ethanol, and then irradiated with 365nm ultraviolet light for 5min. Thus, the flexible structural color-fluorescent composite film II is obtained.

[0060] Example 6 The basic properties of the flexible structural color-fluorescence composite film described in the present invention.

[0061] The reflection spectra, stress-strain curves and fluorescence spectra of the flexible structural color-fluorescent composite films prepared in Example 1 and Example 2 were tested respectively, and the testing methods were as follows: The reflectance spectrum was obtained by the reflectance mode test of Lambda 750S UV-visible-near-infrared spectrophotometer from PerkinElmer, USA. The test wavelength range was 380nm~850nm, and the data interval was 1nm; The stress-strain curves were obtained by using a universal electronic testing machine from MTS Systems, USA, at room temperature; The fluorescence spectrum was obtained by using the Fluorolog-QM visualized steady-state fluorescence spectrum measurement system of HORIBA Company of Japan. The excitation wavelength was 365nm, the test wavelength range was 400nm~600nm, and the data interval was 1nm.

[0062] The test results are as attached Figure 3 and attached Figure 4 shown.

[0063] By the attached Figure 1 and attached Figure 2 It can be seen that the preparation method described in the present invention can obtain a flexible structural color-fluorescent composite film with uniform structural color and good apparent state. The film has bright colors, can be directly written or patterned, and has good foldable flexibility.

[0064] By the attached Figure 3 As can be seen in (a), the flexible structural color-fluorescent composite film has a distinct reflection peak, which is consistent with its bright color; after being immersed in the quaternary ammonium acrylate solution for the second time, the reflection peak is slightly red-shifted, proving that the quaternary ammonium acrylate has penetrated into the film, resulting in an increase in its helical pitch P. Figure 3 As can be seen in (b), the flexible structural color-fluorescent composite film has an elongation at break of more than 15%, and a tensile strength of about 15MPa; after the second immersion, the tensile strength significantly increased to about 24MPa. Although the elongation at break decreased, it still had an elongation at break of about 10%. Figure 4 It can be seen that when soaked in alkaline solution, the flexible structural color-fluorescent composite film exhibits obvious blue fluorescence under ultraviolet light excitation. When soaked in acid solution again, the blue fluorescence intensity decreases, and the fluorescence spectrum has no obvious characteristic peaks, which shows that the film can be directly written with alkaline solution, and the written content can be quickly erased with acid solution, and the process can be repeated. Figure 5 The alkali direct-written fluorescent pattern of the flexible structural color-fluorescent composite film was demonstrated, and the fluorescence intensity of the obtained pattern had the characteristics of first increasing and then decaying, which proved the time-dependent fluorescence characteristics of the flexible structural color-fluorescent composite film. Combining the above performance results, it can be concluded that the flexible structural color-fluorescent composite film has good flexibility and bright structural color, as well as time-dependent blue fluorescence performance, and can be quickly and repeatedly erased by acid and alkali solutions. This means that it has the potential to be applied in the fields of information storage and anti-counterfeiting encryption.

[0065] Example 7 Application of the flexible structural color-fluorescence composite film of the present invention.

[0066] Attached Figure 6 and attached Figure 7 The flexible structural color-fluorescence composite film is used as a functional material for information storage and anti-counterfeiting encryption. Figure 6It can be found that, through the mask method, the two-dimensional code pattern with graphic information can be transferred to the flexible structural color-fluorescent composite film by ultraviolet light, and the two-dimensional code can be directly scanned and recognized by a mobile phone to obtain the recorded two-dimensional code information, which shows that the flexible structural color-fluorescent composite film can be used for information storage. Figure 7 It can be seen that the ciphertext is hidden on the flexible structural color-fluorescent composite film by using binary coding, and after being soaked in an alkaline solution, the coded ciphertext can be clearly identified under ultraviolet light, and then the encrypted information can be extracted by decoding. This example shows that the flexible structural color-fluorescent composite film can be used as an information anti-counterfeiting encryption material.

[0067] The above description of the embodiments is to facilitate those of ordinary skill in the art to understand and apply the present application. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.

Claims

1. A method for preparing a time-dependent and rewritable flexible cellulose nanocrystal composite film, characterized in that: The preparation method comprises the following steps: Step S1: preparing a cellulose nanocrystal film with structural color; Mixing a required weight of a water-dispersible cellulose nanocrystal suspension, a first crosslinking agent, a first surfactant, a coumarin compound, and a first photoinitiator to form a uniform mixed suspension, and drying to obtain a cellulose nanocrystal film with structural color; Step S2: preparing a time-dependent and rewritable flexible cellulose nanocrystal composite film; placing the structurally colored cellulose nanocrystal film obtained in step S1 under ultraviolet light for a first crosslinking reaction to obtain the time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film; Step S3: preparing a time-dependent and rewritable flexible cellulose nanocrystal composite film treated with quaternary ammonium salt; Soaking the time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film obtained in step S2 with a soaking liquid, and then placing it under ultraviolet light for a second cross-linking reaction to obtain a quaternary ammonium salt-treated time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film; Wherein, the soaking liquid is made of a second cross-linking agent, a quaternary ammonium salt ionic liquid, a second photoinitiator and an aqueous mixed solvent.

2. The preparation method according to claim 1, characterized in that In step S1, a water-dispersed cellulose nanocrystal suspension is prepared from cellulose by a mature sulfuric acid hydrolysis method, and its mass fraction accounts for 50-90% of the total mass of the raw materials added in this step; In step S1, the coumarin compound is one or more of the compounds described in the following structural formulas (I) to (IV), and the mass fraction of the total mass of the raw materials added in this step is 0.5% to 7.5%: ; In step S3, the quaternary ammonium salt ionic liquid is one or both of quaternary ammonium acrylate and quaternary ammonium methacrylate, and the mass fraction of the total mass of the raw materials added in this step is 10% to 60%, and the structure of the quaternary ammonium salt ionic liquid is shown as follows: ; Wherein, m is an integer of 1 to 4, R1 is H or methyl, R2, R3 and R4 are methyl, ethyl, propyl, butyl or benzyl, and R2, R3 and R4 may be the same or different, and X is chlorine or bromine.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the first cross-linking agent is one or both of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate, the average relative molecular mass of the first cross-linking agent is 200 g / mol-4000 g / mol, and the mass fraction of the first cross-linking agent in the total mass of the raw materials added in this step is 5%-30%; In step S1, the first surfactant is at least one of alkyl sulfates with carbon atoms of 8-18, alkyl sulfonates with carbon atoms of 8-18, and alkylbenzene sulfonates with carbon atoms of 8-18, and the mass fraction of the first surfactant in the total mass of the raw materials added in this step is 0% to 8%; In step S1, the first photoinitiator is any commercially available universal ultraviolet photoinitiator, and its mass fraction accounts for 0.5% to 4.5% of the total mass of the raw materials added in this step.

4. The preparation method according to claim 1 or 2, characterized in that: In step S3, the second cross-linking agent is one or both of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate, the average relative molecular mass of the second cross-linking agent is 200 g / mol-4000 g / mol, and the mass fraction thereof in the total mass of the raw materials added in this step is 0.5%-5%; In step S3, the second photoinitiator is any commercially available universal ultraviolet photoinitiator, and its mass fraction in the total mass of the raw materials added in this step is 0.1% to 1%; In step S3, the aqueous mixed solvent is a mixture of water and dimethyl sulfoxide.

5. The preparation method according to claim 1 or 2, characterized in that: In step S3, the soaking time is 6 to 72 hours, and reduced pressure or vacuum soaking is adopted.

6. The preparation method according to claim 1 or 2, characterized in that: In step S3, when the second cross-linking reaction is performed, the ultraviolet light irradiation time does not exceed 0.5 hours.

7. A time-dependent and rewritable flexible cellulose nanocrystal composite film, which is prepared by the preparation method according to any one of claims 1 to 6.

8. An information storage material comprising the time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film as claimed in claim 7.

9. An anti-counterfeiting encryption material comprising the time-dependent and repeatedly erasable flexible cellulose nanocrystal composite film as claimed in claim 7.

10. An anti-counterfeiting encryption method, characterized in that: The anti-counterfeiting encryption method comprises the following steps: storing the information to be hidden on the anti-counterfeiting encryption material as claimed in claim 9, then soaking the anti-counterfeiting encryption material with an alkaline solution, and displaying the information to be hidden under ultraviolet light.

Citation Information

Patent Citations

  • Repeatably erasable photonic crystal structure color-based anti-counterfeiting film and preparation method and application thereof

    CN111040225A

  • Flexible waterproof cellulose liquid crystal membrane and preparation method thereof

    CN115895044A

  • Preparation method and application of multi-stimulus response anti-counterfeiting paper based on chestnut shells and coumarin

    CN118639461A

  • Stretching discoloring flexible cellulose liquid crystal composite film as well as preparation method and application thereof

    CN118994695A